2009
DOI: 10.1080/03601230902728245
|View full text |Cite
|
Sign up to set email alerts
|

Degradation behavior of sulfadiazine in soils under different conditions

Abstract: This study investigated the degradation of sulfadiazine in three soils and also determined its sorption and hydrolysis behaviors as well. At the spike concentration of 10 mg/kg, the half-lives for sulfadiazine in the aerobic nonsterile soils ranged from 12 days to 18 days. Sulfadiazine was more persistent in the anoxic soils with the half-lives ranging between 57 days and 237 days and soil microorganisms played little role in the dissipation process under anoxic conditions. The decline in sulfadiazine concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 32 publications
3
35
0
3
Order By: Relevance
“…Thus, the low pH value of 5.7 in the KAL soil enabled sorption as the neutral and cationic SDZ species developed, while in the MRZ soil with a pH of 7, sorption was distinctively lower as the anionic SDZ form dominated. The strong impact of pH on sorption of sulfonamides was also pointed out by Yang et al (2009), who observed that sorption of SDZ decreased to zero even in soils with a high organic matter content of up to 3% at pH values of 7.2. In summary, and according to Kahle and Stamm (2007), sorption of SDZ depends strongly on i) the soil type (a content of organic material) and ii) the prevailing pH value.…”
Section: Small-scale and Short-term Sorption And Degradation Of Sdzsupporting
confidence: 53%
See 1 more Smart Citation
“…Thus, the low pH value of 5.7 in the KAL soil enabled sorption as the neutral and cationic SDZ species developed, while in the MRZ soil with a pH of 7, sorption was distinctively lower as the anionic SDZ form dominated. The strong impact of pH on sorption of sulfonamides was also pointed out by Yang et al (2009), who observed that sorption of SDZ decreased to zero even in soils with a high organic matter content of up to 3% at pH values of 7.2. In summary, and according to Kahle and Stamm (2007), sorption of SDZ depends strongly on i) the soil type (a content of organic material) and ii) the prevailing pH value.…”
Section: Small-scale and Short-term Sorption And Degradation Of Sdzsupporting
confidence: 53%
“…Anskjaer et al (2014) observed a general trend of increasing sorption at low pH and decreasing sorption at high pH for clayey sand and silty clay and a wide range of pH values between 4.3 and 7.6. Yang et al (2009) also detected that SDZ degradation did not occur in anoxic or sterile soils, and thus that a higher microbial activity plays a key role in the SDZ degradation since it was observed to be highest in the sandy MRZ soil.…”
Section: Small-scale and Short-term Sorption And Degradation Of Sdzmentioning
confidence: 91%
“…Studies of SDZ degradation published so far mainly refer to the dissipation of the parent substance in the respective environments or test systems (22)(23)(24) and to the identification of transformation products (23,25,26). Mineralization appears to be insignificant, since experiments with 14 C-labeled SDZ revealed that only a small fraction (less than 2%) was mineralized to CO 2 within moderate time periods (maximum, 218 days) (18).…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, para as SAs em geral, a literatura cita valores médios variando de 0,6 a 7,4 L kg -1 (SARMAH et al, 2006), o que sugere baixo a moderado potencial de sorção para esta classe de antibióticos nos solos estudados e enfatiza seu potencial de mobilidade no perfil do solo, podendo atingir corpos de água subterrâneos (HIRSCH et al, 1999). Infelizmente, a maioria dos trabalhos adotou concentrações iniciais de antibióticos muito maiores do que aquelas relevantes ambientalmente (>> 100 µg kg -1 ) (THIELE-BRUHN et al, 2004;ACCINELLI et al, 2007;SUKUL et al, 2008;YANG et al, 2009) (BOXALL et al, 2002). Entretanto, a grande maioria desses trabalhos adotaram solos formados sob condições de clima temperado, apresentando maiores valores de pH ( > 6), o que culmina na desprotonação da molécula e repulsão eletrostática com os coloides do solo carregados negativamente.…”
Section: (µG/g De Solo) = (Cf -Cnf)/kcunclassified
“…O efeito do tempo residual de uma molécula no seu potencial de retenção no solo é descrito como envelhecimento, definido como um processo lento de sorção ao solo, podendo ser irreversível ou parcialmente reversível e, portanto, formando uma fração residual (não-extraível) no solo (PIGNATELLO, 1999), também denominada de resíduos ligados (RLs) (GEVAO et al, 2000). Deste modo, podemos dizer que a formação de RLs representou a principal forma de dissipação da SDZ, responsável pela transferência da molécula da solução para a matriz sólida do solo, compondo o seu sumidouro final primário HOLTGE, 2005;HEISE et al, 2006;YANG et al, 2009). De fato, são frequentes os relatos sobre o efeito do envelhecimento da SDZ em solos e estercos (THIELE-BRUHN et al, 2004;KAY et al, 2004;SCHAUSS, 2009), assim como para a maioria dos antibióticos veterinários (KUMMERER, 2008).…”
Section: Dissipaçãounclassified